If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 19 = -30 Reorder the terms: 19 + 6x = -30 Solving 19 + 6x = -30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 6x = -30 + -19 Combine like terms: 19 + -19 = 0 0 + 6x = -30 + -19 6x = -30 + -19 Combine like terms: -30 + -19 = -49 6x = -49 Divide each side by '6'. x = -8.166666667 Simplifying x = -8.166666667
| 3x-9=5x+15 | | 14x-9=21+4x | | 3t+4t=51-8 | | (-5)+4=x-3 | | 3(u+3)=-6(4u-1)+9u | | (6x+40)-2x=(2x+116)-2x | | y-11=-17 | | (5x+10)-3x=(3x+36)-3x | | 6m-9=21 | | -.25x+8=12+-5 | | 3y=12x+3+39 | | ln(6y+2)-ln(y+1)=ln(2y-1) | | -7(-4w+9)-7w=7(w-7)-7 | | (X+1)(x-1)-(x-1)=0 | | (4x+18)-2x=(2x+36)-2x | | -x-10+2x=18 | | 10x-7=(-4x)+5 | | 2(s+3)=12 | | 18=7s+2a | | (7x+15)-2=(2x+70)-2 | | 10x+30+2x+18=180 | | 10=2r | | x^2+y^2-2xy+2y+1=0 | | 4sin^2(3x)=3 | | -15+10=-5y | | 4x+2=2x+4x+12 | | (8x+44)-4=(4x+76)-4 | | 3x+15+7x+5=180 | | 12x^2-84x=0 | | (2x^2+3x-8)+(5x^2-9x+2)= | | 7y-4=4y+14 | | -.25x+8=12+-7 |